Empowering citizens through data interoperability: data federation applied to consumer-centric healthcare - Tiina Anneli Nokkala; Tomi Dahlberg (Sosiaali- ja terveyshuollon tietojenkäsittely-yhdistys, 2022)
During the era of open systems, healthcare services and related data are in a constant flux caused by digital transformation. The amount, sources and dimensionality of data grow rapidly, and solutions for data governance, integration and interoperability are urgently needed. At the same time, digital data and information technology–enabled healthcare services are offered as a means to empower citizens. The objective is for active citizens to take better care of their own health. It is possible to support empowerment in many ways, such as with easy-to-use information systems (IS) or personal health records (PHR), or by supporting citizens’ participation in health data creation. In this article, we first present the federative approach to data governance with data federation matrixes in order to show how data are made interoperable by combining data from different data storages. Federation matrixes define shared attributes with their technical, information-flow and socio-contextual metadata. We then contemplate how the federative approach can be deployed to citizens’ healthcare data empowerment. We propose that data ontologies, e.g., data federation matrixes, are useful in bridging gaps between the social contexts of citizens and healthcare professionals and, by doing so, to promote citizen empowerment. The present article contributes to research on the federative approach to data governance, its deployment to citizens’ healthcare empowerment, and to the practice-oriented further development of the federation matrix tools for this and other use cases.